Implementation of the PHBS movement indicators in a health and Islamic perspective in Medangan Hamlet, Magelang - Eka Sakti Wahyuningtyas; Nafis Avi Lavirda; Muhammad Dzaky Fakhruddin; Erinda Tri Iswati; Indah Saputri Dewi; Zuba Nur Arifah (Universitas Muhammadiyah Magelang, 2023)
Clean and Healthy Living Behavior (PHBS) is health behavior that is carried out out of awareness so that individuals or family members can help themselves and can play an active role in health activities in the community. According to Islam, health is defined as a good condition for all members of the body and afiat is defined as the protection of Allah SWT for His servants. The low level of knowledge of the people of Medangan Hamlet, Tersan Gede Village, regarding indicators of Clean and Healthy Behavior (PHBS) can raise the risk of disease spread and morbidity. The purpose of this community service is to implement the PHBS movement in a health and Islamic perspective. The methods in this program are community development, educative, and participatory. The results of this program indicate an increase in knowledge, changes in lifestyle behavior to become healthier as evidenced by the community's habit of washing their hands properly, getting used to not defecating in any place and sorting waste.